Strategy of Empowerment and Marketing of Bridal Crafts (Tamiyang) - Bayu Maulana (Journal of Islamic Economy and Community Engagement, 2021)
The purpose of this research is to provide training in marketing broom handicraft products in Mekarjaya Village, Padamulya Village, where the artisans have problems and many people in the area do not know yet in the process of marketing activities. The approach taken to solve this problem uses a mentoring method in the form of marketing training. The results of the assistance and training program in improving the ability to manage broom products for the people of Padamulya Village can be seen from the change in mindset of the craft owners from those who previously only marketed their products in their home regions but now can expand their market share widely by using current technology, namely applications buying and selling online. In addition, people are starting to understand the importance of brands that affect sales.Keywords: Management, Marketing, Handicraft Product